THE EFFECT OF TAX AGGRESSIVENESS AND PROFITABILITY ON ACCOUNTING FRAUD - Indah Umiyati; Sri Mulyati; Rika Nandini (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2024)
Fraud is a deliberate attempt to use the rights of others for personal gain. Accounting fraud is a misstatement that arises from fraud in financial reporting, namely a misstatement or intentional omission of amounts or disclosures in financial statements to deceive users of financial statements. This research was conducted to determine the effect of Tax Aggressiveness and Profitability on Accounting Fraud. The research objects used in this study are companies in the manufacturing sector that are listed on the Indonesia Stock Exchange from 2017 to 2021. The number of samples used in this study are 120 firm-years. Tax Aggressiveness Variable is measured using CETR, Profitability is measured using ROA and Accounting Fraud is measured using the Beneish M Score Method. Logistic regression was used to test the hypothesis. The results of this study indicate that tax aggressiveness has a positive effect on accounting fraud. While profitability has a negative effect on accounting fraud.